Therapeutic Potential of Tea (Camellia sinensis) Against Oral and Intestinal Microbial Flora - Mishra, Anita; Alia, Aparna (International Journal of Applied Sciences and Biotechnology, 2021)
The tea powder produced from plant Camellia sinensis (L), is popular as a daily beverage drink among the Indian population. The tea plant produces large number of metabolites which are of medicinal value. In the present study, the activity of tea leaf extract was studied by disk diffusion method against the bacterial strains, Streptococcus mutans, Enterobacter fecalis, Escherchia coli, Staphylococcus aureus and Psudomonas aeruginosa isolated from the oral swab. From the disk diffusion assay, the tea extract has shown better activity against S. mutans and P. aeruginosa at the concentration, 25 mg/ml. It is effective agaisnt E. fecalis and S. aureus at higher concentration, 75 mg/ml and 100 mg/ml. Thus, the tea leaf can be considered as effective antibacterial agent against the oral pathogens. Int. J. Appl. Sci. Biotechnol. Vol 9(2): 107-112. .